PENGARUH KOMISARIS INDEPENDEN, LEVERAGE, INTENSITAS PERSEDIAAN, INTENSITAS ASET TETAP DAN UKURAN PERUSAHAAN TERHADAP AGRESIVITAS PAJAK PADA WAJIB PAJAK BADAN (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2014-2016) - Eka Fitri Nor Nor Wahyuni; Vince Ratnawati; Rusli Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
The purpose of this research is to examine the effect of independent commissioner, leverage, inventory intensity, fixed assets intensity, and size on tax aggressiveness. The population is all manufacturing companies that listed in the Indonesia Stock Exchange Periode 2014-2016. Using purposive sampling method, 34 companies are selected as samples. Data analysis techniques used in this research was multiple linear regression analysis using Statistical Product and Service Solution (SPSS) version 22.0 for Windows as data processing software program. The result of this research show independent commissioner, leverage, and fixed assets intensity have an effect on tax aggressiveness, while inventory intensity and size does not have an effect on tax aggressiveness. Based on calculation of coefficient determination (R2 ) was 0,213. Independent commissioner, leverage, inventory intensity, fixed assets intensity, and size simultaneously giving effect was 21,3%. While the remaining 78,7% is influenced by other independent variable that are nor observed in this research.Keywords : Independent Commissioner, Leverage, Inventory Intensity, Fixed Assets Intensity, Size and Tax Aggressiveness